2021
DOI: 10.1159/000518015
|View full text |Cite
|
Sign up to set email alerts
|

Topical α-Gal Nanoparticles Enhance Wound Healing in Radiated Skin

Abstract: Surgery within radiated tissue is associated with increased complication rates. It is hypothesized that impaired wound healing may result from aberrant inflammatory responses that occur in previously radiated tissues. Previous work has demonstrated that the topical application of naturally occurring antigen α-gal (Galα1-3Galβ1-(3)4GlcNAc-R) nanoparticles (AGNs) within wounds accelerates macrophage recruitment and subsequent healing in both normal and diabetic wounds. Herein, we hypothesize that application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Irradiated wounds that failed to close by POD21 were harvested the following day and were considered "non-healing". This determination was based on prior studies and our own pilot wounding studies, which indicated that healing would no longer progress after POD21 as re-epithelialization had occurred but wounds were too fragile, preventing complete healing and full closure [10]. Harvested wounds were fixed in 10% neutral buffered formalin overnight, embedded in paraffin, and then sectioned into 8 μM thick sections.…”
Section: Tissue Harvestmentioning
confidence: 99%
See 2 more Smart Citations
“…Irradiated wounds that failed to close by POD21 were harvested the following day and were considered "non-healing". This determination was based on prior studies and our own pilot wounding studies, which indicated that healing would no longer progress after POD21 as re-epithelialization had occurred but wounds were too fragile, preventing complete healing and full closure [10]. Harvested wounds were fixed in 10% neutral buffered formalin overnight, embedded in paraffin, and then sectioned into 8 μM thick sections.…”
Section: Tissue Harvestmentioning
confidence: 99%
“…This is notable as dermal hypovascularity, a hallmark of RIF, is responsible for reduced nutrient supply and is likely a key contributor to the impaired wound healing seen in irradiated skin [35]. Prior murine studies have demonstrated a similar correlation between increased angiogenesis and improved healing outcomes in irradiated wounds [10,12]. Clinically, good perfusion is a sine qua non for wound healing.…”
Section: Deferoxamine Improves Wound Perfusion and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The repair of wounds by α-gal nanoparticles was found to be potent enough to also occur in diabetic mice with chronic wounds which do not heal without such treatment (Galili, 2017;Kaymakcalan et al, 2020). This potent healing effect was further demonstrated in mouse radiation wounds in which topical application of α-gal nanoparticles resulted in faster wound healing than the delayed wound healing usually seen in irradiated skin (Samadi et al, 2021). The accelerated wound healing by α-gal nanoparticles was validated in the large experimental animal model of GT-KO pigs (Hurwitz et al, 2012).…”
Section: Accelerated Healing and Regeneration Of Skin Injuries By α-Gal Nanoparticlesmentioning
confidence: 92%
“…Wound and burn healing by α-gal nanoparticles —the effects of α-gal therapy by α-gal nanoparticles were studied on skin injuries ( Galili et al, 2010 ; Wigglesworth et al, 2011 ; Kaymakcalan et al, 2020 ; Galili, 2017 ; Kaymakcalan et al, 2018 ; Samadi et al, 2021 ; Hurwitz et al, 2012 ). Application of α-gal nanoparticles to full-thickness wounds or burns of anti-Gal–producing GT-KO mice decreased the healing time by ∼50% in comparison to wound healing time in untreated GT-KO mice.…”
Section: Immunological Processes Associated With Anti-gal/α-gal Epitope Interactions Which May Be Harnessed For α-Gal Therapiesmentioning
confidence: 99%